Predicting Empathy From Resting State Brain Connectivity: A Multivariate Approach - Christov-Moore, Leonardo; Reggente, Nicco; Douglas, Pamela K.; Feusner, Jamie D.; Iacoboni, Marco (Frontiers in Integrative Neuroscience, 2020)
Recent task fMRI studies suggest that individual differences in trait empathy and empathic concern are mediated by patterns of interaction between self-other resonance and top-down control networks that are stable across task demands. An untested implication of this hypothesis is that these stable patterns of interaction should be visible even in the absence of empathy tasks. Using machine learning, we demonstrate that patterns of resting state fMRI connectivity (i.e. the degree of synchronous BOLD activity across multiple cortical areas in the absence of explicit task demands) of resonance and control networks predict trait empathic concern (n=58). Empathic concern was also predicted by connectivity patterns within the somatomotor network. These findings further support the role of resonance-control network interactions and of somatomotor function in our vicariously-driven concern for others. Furthermore, a practical implication of these results is that it is possible to assess empathic predispositions in individuals without needing to perform conventional empathy assessments.